Experiments on multi-nucleon transfer reactions with the systems 58,64Ni + 207Pb at SHIP - Comas Lijachev, Victor Fernandovich; Justus Liebig University Giessen (My University, 2012)
This work presents experimental results on multi-nucleon transfer reactions in the collision systems 58Ni+207Pb and 64Ni+207Pb which were measured at the velocity filter SHIP at GSI. The reactions were performed at beam energies below and up to 10% above the Coulomb barrier. The work was motivated by theoretical predictions to apply multi-nucleon transfer reactions in heavy systems to synthesize new neutron-rich isotopes in the region of superheavy nuclei with Z>100 and in the region of the closed neutron shell N=126. The expected cross-sections for the production of these nuclei in transfer reactions are small and reach typically nanobarn and below. Therefore, efficient separation techniques have to be applied and the detection system must allow for the identification of single nuclei. A dedicated experimental setup to study such rare transfer products does not exist presently. But already existing facilities which are used for the synthesis of superheavy fusion products meet the requirements for the detection of rare reaction products. In this context, the velocity filter SHIP offers the possibility to separate heavy target-like transfer products from projectiles and projectile-like reaction products before they reach the detection system where the particles are identified by their alpha-decay properties. At SHIP, a cross-section limit of 10 pb can be reached at usual beam intensities.In the present work on collisions of 58,64Ni+207Pb the influence of the projectile neutron number on the cross-sections, isotopic distributions and excitation energies of the transfer products was studied. Especially with the more neutron-rich 64Ni projectiles a transfer of up to seven protons and eight neutrons to the target nucleus was observed. The largest cross-sections for the most neutron-rich isotopes were reached at the beam energies around the Coulomb barrier.The transfer was accompanied by the full dissipation of the available kinetic energy indicating the deep inelastic nature of the process. A strong influence of shell effects, particularly of the closed neutron shell at N=126, on the excitation energy of the transfer products was seen at the lowest beam energies.A comparison of the measured cross-sections with calculations in the two-centre shell model with adiabatic potentials showed that the model underestimates the cross-sections by at least one order of magnitude.Strong similarities in the excitation functions of transfer products and superheavy fusion products were revealed by the data. This is consistent with the picture of the two-centre shell model which assumes that fusion is initiated by transfer. Apart from the above described results, the data offered the possibility to determine nuclear interaction times in a rather direct way due to the observation of 180 degree rotations of the nuclear systems composed by the sicking projectile and target nucleus.
Experimente zu Multinukleon-Transferreaktionen im System 58,64Ni + 207Pb mit SHIP
Keywords: Tiefinelastische Transferreaktionen; Superschwere Kerne; Deep inelastic transfer reactions; superheavy nuclei; ddc:530